Advancing Geohazard Mapping and Monitoring Using Terrestrial LiDAR: Insights from the British Geological Survey - Jones, Lee D (Geography, Earth Science and Environment: Research Highlights Vol. 9, 2025)
Geomatics is defined in the ISO/TC 211 series of standards as the discipline concerned with the collection, distribution, storage, analysis, processing and presentation of geographic data or geographic information. It is the discipline of electronically gathering, storing, processing and delivering spatially related digital information; it continues to be one of the fastest expanding global markets, driven by technology. The aim of this chapter is to review the types of work that the BGS carries out using terrestrial and aerial LiDAR systems, and to discuss the merits therein. The British Geological Survey (BGS) geomatics capabilities have been utilized in a variety of scientific studies such as the monitoring of actively growing volcanic lava domes and rapidly retreating glaciers; coastal erosion and platform evolution; inland and coastal landslide modelling; mapping of geological structures and fault boundaries; rock stability and subsidence feature analysis and geo-conservation. In 2000, the BGS became the first organization outside the Mining Industry to use Terrestrial LiDAR Scanning (TLS) as a tool for measuring change; paired with a Global Navigation Satellite System (GNSS), BGS were able to measure, monitor and model geomorphological features of landslides in the United Kingdom (UK) digitally. Many technologies are used by the BGS to monitor the Earth, employed on satellites, aeroplanes, drones and ground-based equipment, in both research and commercial settings to carry out mapping, monitoring and modelling of Earth surfaces and processes. Outside BGS, these technologies are used for close-range, high-accuracy applications such as bridge and dam monitoring, crime and accident scene analysis, forest canopy and biomass measurements and military applications. Key methodologies in TLS are discussed under the headings of Mobile Mapping, Monitoring Change, Virtual Outcrop Modelling and Uncrewed Technologies, featuring examples of work for each. This research underscores TLS's transformative potential in geosciences, particularly for advancing disaster resilience, environmental monitoring, and geological conservation efforts. Terrestrial Laser Scanning (TLS) offers high-resolution, three-dimensional data collection capabilities that can significantly enhance the understanding of geological processes and environmental changes.